Ewolucja obrazów totalitaryzmów XX wieku na przykładzie filmów fabularnych oraz seriali telewizyjnych - Łęcicki, Grzegorz (Studia Theologica Varsaviensia, 2018)
The Images of the Twentieth Century Totalitarianism as They Evolved in Film and TV Productions - Summary The author presents the evolution of the cinematic images of twentieth century totalitarianism in selected European feature films as well as in television productions. He analyses the rendition of images of communism in the Soviet, Polish, Slovak, Czech, Romania, and German films. He also tackles the place of propaganda in films made in the fascist Italy and then in Nazi Germany. In that context, he points to the elements of ropaganda in modern cinema of the states that have gone through different stages of totalitarianism.